Pectin Gels Enriched with Dietary Fibre for the Development of Healthy Confectionery Jams - Figueroa, Lilian Elisa (2018)
The objective of this work was to evaluate the effect of dietary fibre from different sources (apple, bamboo, psyllium, and wheat) and pectin content (0.4 and 0.5 g/100 g) on the physicochemical properties of pectin gels, for the development of a novel, healthy product similar to a fruit confectionery jam. A mass fraction of 3 g/100 g fibre was added to each pectin gel, so that the final product could be declared as a source of fibre. It was found that pectin content, type of fibre, and their interaction had a significant effect on the viscoelastic and mechanical properties, and syneresis (water loss) of the gels. Since syneresis of gel with 0.4 g/100 g of pectin was undesirably high, only gels with 0.5 g/100 g of pectin were studied from this point forward. For these gels, fibre addition had a reinforcing effect on the viscoelastic properties (wheat>psyllium>bamboo>apple). Psyllium enriched gels did not suffer any syneresis, although they showed an undesirable gummy aspect, which was associated with some of their mechanical properties. Then, fibre from different sources was combined in pairs (1:1) in order to improve the organoleptic properties of the gels. In general, fibre combination decreased the viscoelastic properties of the gels. However, mixing psyllium with other fibre produced a desirable effect on the mechanical properties of the gels, keeping the syneresis at 0 g/100 g. This indicate that 0.5 g/100 g of pectin and 1.5 g/100 g of psyllium fibre with 1.5 g/100 g of other fibre was the best formulation in terms of the stability and texture of this product.